2020
DOI: 10.1038/s41598-020-79234-w
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of serum amino acid profiles by dietary adenine supplementation inhibits fatty liver development in rats

Abstract: Studies on animal models have demonstrated that feeding a low-arginine diet inhibits triacylglycerol (TAG) secretion from the liver, resulting in marked fatty liver development in rats. Here, we first showed that culturing hepatocytes in the medium mimicking the serum amino acid profile of low-arginine diet-fed rats induced TAG accumulation in the cells, indicating that the specific amino acid profile caused TAG accumulation in hepatocytes. Dietary adenine supplementation completely recovered hepatic TAG secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It is well established that when growing rats are fed a diet in which the protein content is insufficient, or an essential amino acid is lacking, catabolism is enhanced, whereas anabolism is inhibited, resulting in growth retardation. Concurrently, we previously showed that neutral lipids accumulate in the liver of growing rats fed a diet deficient in protein or arginine (3)(4)(5)(6). In addition, a lysine-deficient diet increases the lipid content in the skeletal muscle of pigs (7).…”
Section: Introductionmentioning
confidence: 85%
“…It is well established that when growing rats are fed a diet in which the protein content is insufficient, or an essential amino acid is lacking, catabolism is enhanced, whereas anabolism is inhibited, resulting in growth retardation. Concurrently, we previously showed that neutral lipids accumulate in the liver of growing rats fed a diet deficient in protein or arginine (3)(4)(5)(6). In addition, a lysine-deficient diet increases the lipid content in the skeletal muscle of pigs (7).…”
Section: Introductionmentioning
confidence: 85%
“…In this study, 22 active ingredients in CAROL were identified by UHPLC -QTOF-MS. It has been reported in the literature that these 22 active ingredients have 15 compounds were identified as having ameliorative effects on liver injury, including vanillin, 18 rutin, 19 baicalein, 20 hesperidin, 21 uridine, 22 guanosine, 23 adenine, 24 scopoletin, 25 riboflavin, 26 betaine, 27 narcissoside, 28 baicalin, 29 ursolic acid, 30 betulonic acid, 31 and citric acid. 32 The hepatoprotective effects of CAROL are attributed to these 15 active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Serum metabolite analyses were performed as previously described [ 40 ]. Briefly, 50 μL of serum samples were mixed with methanol to remove macromolecules, such as proteins.…”
Section: Methodsmentioning
confidence: 99%